Reaksi Investor Atas Relevansi Informasi Arus Kas Dan Laba Akrual pada Laporan Keuangan Perusahaan - Muhammad Imam Sundarta; Azolla Degita Azis; Anggita Citra Dewi (Universitas Batanghari Jambi, 2021)
This study aims to determine whether cash flows and accrual earnings affect on stock returns that contained information about investors reaction in manufacturing industries on the Indonesia Stock Exchange from the 2013-2017 period. This research is a quantitative study using secondary data in the form of financial reports. The data analysis technique used is multiple regression analysis. The results of this study indicate that the cash flow statement has no effect on stock returns, while accrual earnings have a positive effect on stock returns. This finding can be one of the additional literature in the field of financial accounting because investors see the earnings information contained in the income statement compared to the cash flow statement that is reflected in stock returns.